(untitled) (Medical Forum Monthly, 2024)
Objective: To study the outcome of surgical treatment of in growing toe nails of feet with and without phenol cauterization at Islam Medical College, Sialkot. Study Design: Prospective study. Place and Duration of Study: This study was conducted at the Department of Dermatology, Islam Medical College, Sialkot from January 2015 to January 2018.. Materials and Methods: All new patients serially treated at that college; fulfilling the inclusion criteria were registered. The patients were classed in two groups: Group I undergoing Surgery only Group II Surgery and Phenol cauterization. The patients with recurrent ingrowing toe nails were also included. Minimum of six months of follow up was must for inclusion in the study. Data was entered and analysis done by SPSS v 22. Results: Total number of patients in study were 283(100%),having Age 15-47 years, with a mean age of 37+_8 years, out of which 205 patients were males & 78 were females, 58(20.49%) patients were Diabetics. Recurrent IGTN were in 43(15.19%) and peripheral vascular disease was in 7(2.47%), Group I patients were 128(45.22%) and Group II had 155(54.77%) patients. We encountered wound infection in 11(8.59%) and 7(4.51%), recurrence in 8(6.25%) and 3(1.93%), persistent pain in 6 (4.68%) and 5 (3.22%) and disfigurement in 2(1.56%) and 7(4.51%) patients in Group I and Group II respectively. Conclusion: The surgical treatment in combination with phenol cauterization has very low recurrence rate as compare to surgery alone.